Twitter Sentiment Analysis with Emoticons (International Journal of Engineering and Computer Science, 2017)
Sentiment analysis, which is also called opinion mining is the field of study which analyzes people’s opinions, sentiments, evaluations, appraisals, attributes and emotions towards entities such as products services, organizations, individuals, issues, events, topics, and their attributes through twitter. People use microblogging (twitter) to talk about their daily activities and to seek or share information. It is an online social networking and micro-blogging service that enables users to send and read "tweets", which are text messages limited to 140 characters. In this paper we propose a model that can spot the public opinion with their emotions.